Sensors, empowerment and accountability (SEMA):Powerpoint - Li, Guorui (University of Twente, 2020)
This lecture presents: Zanzibar - Human Sensor Web; SEMA WPM Mobile Updating System How it works; The Bunda District Case Study; Mobile App Test Results.